Fertility treatments and the risk for ophthalmic complications: a cohort study with 25-year follow-up. (1st October 2016) - Ratson, Roy; Sheiner, Eyal; Davidson, Ehud; Sergienko, Ruslan; Beharier, Ofer; Kessous, Roy
Abstract: Objective : To investigate whether there is an association between a history of fertility treatments and future risk for long-term maternal ophthalmic complications. Study design : A population-based study compared the incidence of long-term maternal ophthalmic complications in a cohort of women with and without a prior history of fertility treatments, including in vitro fertilization (IVF) and ovulation induction (OI). Deliveries occurred between the years 1988–2013, with a mean follow-up duration of 12 years. Women with known ophthalmic diseases prior to the index pregnancy were excluded from the analysis. Ophthalmic complications were further divided to glaucoma, diabetic retinopathy, macular degeneration and retinal detachment. Kaplan–Meier survival curve was used to estimate cumulative incidence of ophthalmic complications. Cox proportional hazards model was used to estimate the adjusted hazard ratios (HR) for ophthalmic complications. Results : During the study period, 106 004 deliveries met the inclusion criteria; 4.1% ( n = 4364) occurred in patients with a history of fertility treatments. Patients with a history of fertility treatments, as a group, did not have a significantly higher incidence of ophthalmic complications. However, the subgroup of patients with a history of IVF (but not OI) had a higher incidence of retinal detachment (0.3% versus 0.1%; p = 0.02). Using a Kaplan–Meier survival curve, patients following IVF had a significantly higher cumulative incidence of retinal detachment. Using Cox proportional hazards models, controlling for maternal age, obesity and parity, IVF was noted as an independent risk factor for retinal detachment (adjusted HR 3.4; 95% 1.2–9.3; p = 0.011). Conclusion : Patients following IVF treatments have a significant higher long-term risk for retinal detachment. OI treatments do not pose a risk for long-term maternal ophthalmic complications.